1996
DOI: 10.1111/j.2044-8325.1996.tb00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and limitations of ipsative measurement

Abstract: The relative merits of ipsative measurement for multi-scale psychometric instruments are discussed. Standard psychometric analyses are found to be inappropriate with small numbers of scales, or sets of scales with strong positive intercorrelations. However, for larger sets of scales ( N -30) with low average intercorrelations, ipsative data seems to provide robust statistical results in reliability analyses but not under factor analysis. It is argued that the potential of forced-choice formats to control for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
172
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(179 citation statements)
references
References 7 publications
3
172
0
4
Order By: Relevance
“…Third, the leader measure employed in the study was ipsative in nature and is therefore only appropriate for categorizing leaders into preferred types (Baron, 1996;Chan, 2003). More directly, total scores on the various leader types (e.g., a participant's degree of pragmatic leadership) could not be obtained.…”
Section: Limitationsmentioning
confidence: 99%
“…Third, the leader measure employed in the study was ipsative in nature and is therefore only appropriate for categorizing leaders into preferred types (Baron, 1996;Chan, 2003). More directly, total scores on the various leader types (e.g., a participant's degree of pragmatic leadership) could not be obtained.…”
Section: Limitationsmentioning
confidence: 99%
“…Principal components analysis can be performed on ipsative scores; however, it may yield quite different results from the analysis of corresponding normative scores. Ipsativity produces artifactual bipolar components, where traits that would typically belong to different components in normative data are contrasted to each other Baron, 1996). Ipsativity, therefore, clearly compromises construct validity of forced-choice questionnaires.…”
Section: Distorted Construct Validitymentioning
confidence: 99%
“…For instance, Baron (1996) argued that coefficient alpha underestimates internal consistency reliabilities in MFC questionnaires measuring a large number of scales. On the contrary, Johnson, Wood and Blinkhorn (1988) suggested that reliabilities of ipsative tests overestimate the actual scale reliabilities.…”
Section: Distorted Reliability Estimates How Irt Can Solve Problems Omentioning
confidence: 99%
See 1 more Smart Citation
“…In psychological research the ipsative style has been used to avoid the potential for central tendency bias with a Likert response format, as respondents avoid the most extreme categories (Baron, 1996, Christiansen et al, 2005. Other potential biases with Likert scales include acquiescence responding, where responders tend to agree with statements and social desirability responding where they try to appear more positive (and occasionally more negative) than they are.…”
Section: Assessment Scalementioning
confidence: 99%